Evolution and challenges of DDR: A policy review through the prism of Colombia's DDR experience - Rodríguez-Castellón, José Miguel; Justus Liebig University Giessen (My University, 2024)
Disarmament, demobilization, and reintegration (DDR) processes have undergone significant evolution in recent decades, reflecting the complex dynamics of the transition from conflict to peace. This paper presents a comparative analysis of three generations of DDR processes, illustrating the shift from a primarily security-focused approach to a comprehensive strategy that includes socioeconomic development, political participation, and community engagement. In Colombia, a country with a long history of armed conflict, the process of DDR has undergone significant changes. These changes were made to adapt to the intricate realities of war, peace agreements, and social integration. During its evolution, DDR in Colombia has encountered challenges in expanding beyond the traditional scope of disarmament and demobilization to include the crucial aspect of reintegration. This highlights the significance of addressing the varied needs of ex-combatants and ensuring their sustainable integration into civilian life. The findings emphasize the importance of flexible and context-sensitive DDR frameworks that acknowledge the distinct challenges and opportunities of each post-conflict scenario. This provides valuable insights for future peacebuilding efforts worldwide.
Keywords: ddc:300